Powered by Immersion? Examining Effects of 360-Degree Photography on Knowledge Acquisition and Perceived Message Credibility of Climate Change News. Issue 3 (2nd April 2020) - Greussing, Esther
ABSTRACT: Research on the effects of climate change imagery has mainly focused on traditional photographs or infographics, thereby neglecting other visual presentation forms increasingly used in today's digital landscape. Hence, this study investigates how an immersive 360-degree photograph affects individuals' knowledge acquisition and perceived message credibility when being embedded in text-based climate change coverage. To isolate the modality features driving potential effects, the 360-degree photograph is contrasted with two less immersive visualization forms (video and still photo). News readers' issue-specific prior knowledge, topic involvement, and level of environmental concern were considered as potential moderators. Results of an online survey experiment ( N = 401) reveal detrimental effects for adding 360-degree technology to text-based news on knowledge acquisition and provide no evidence for effects on perceived message credibility. Moreover, the effects do not vary among levels of the three moderators under study. The implications of these limited effects for environmental communication are discussed.